Pelatihan Pembuatan Pupuk Hayati pada Sistem Agroforestri berbasis Kopi di Desa Garahan, Jember, Jawa Timur - Yunik Istikorini; Muhammad Alam Firmansyah; Lufthi Rusniarsyah; Ikhwan Shodiq; Tiska Aulia Azzahra; Idelia Latifah (Institut Pertanian Bogor, 2023)
The productivity of coffee plants on the most cultivated land in Garahan Village decreased. This decline is thought to be caused by, among others, climate change, land degradation and the presence of pests and diseases in coffee plants. This training aims to introduce pests and diseases in coffee-based agroforestry to farmers and develop environmentally friendly biofertilizers. This activity begins with a pre-test, socialization and training and ends post-test. Based on the survey and direct observation, coffee plants found upas fungal diseases, root diseases, and stem borer pests. The agroforestry system applied is complex and straightforward agroforestry. In complex agroforestry, coffee plants are grown with various other crops, such as pepper, vanilla, leucaena, taro, banana, gamal, and mahogany. Simple agroforestry consists of coffee land planted with single-shade crops such as leucaena and gamal or a combination of Leucaena and pine. The training results showed an increased farmer's better understanding of coffee pests and diseases, the benefits of agroforestry, and the manufacture of biofertilizers. The biofertilizer developed is expected to increase the productivity of coffee plants.